The role of CYP2C19 genotyping to guide antiplatelet therapy following ischemic stroke or transient ischemic attack. Issue 7 (3rd July 2022) - McDermott, John H; Leach, Marc; Sen, Dwaipayan; Smith, Craig J.; Newman, William G.; Bath, Philip M.
ABSTRACT: Introduction: Clopidogrel is an antiplatelet agent recommended for secondary prevention of ischemic stroke (IS) and transient ischemic attack (TIA). Conversion of clopidogrel to its active metabolite by hepatic cytochrome P450-2C19 (CYP2C19) is essential for the inhibition of the P2Y12 receptor and subsequent platelet aggregation to prevent thrombotic events. CYP2C19 is highly polymorphic, with over 30 loss of function (LoF) alleles. This review considers whether there is sufficient data to support genotype guided antiplatelet therapy after stroke. Areas covered: A systematic literature review retrieved articles, which describe the interaction between CYP2C19 genotype and clinical outcomes following IS or TIA when treated with clopidogrel. The review documents efforts to identify optimal antiplatelet regimens and explores the value genotype guided antiplatelet therapy. The work outlines the contemporary understanding of clopidogrel metabolism and appraises evidence linking CYP2C19 LoF variants with attenuated platelet inhibition and poorer outcomes. Expert opinion: There is good evidence that CYP2C19 LoF allele carriers of Han-Chinese ancestry have increased risk for further vascular events following TIA or IS when treated with clopidogrel. The evidence base is less certain in other populations. The expansion of pharmacogenetics into routine clinical practice will facilitate further research and help tailor other aspects of secondary prevention.